Modeling Chat System Between Internet Relay Chat (IRC) and Caster Within A Live Streaming Platform - H Hassanah; A J Sabur; M L Nurjaya; A Jayabinangun; Maulidina Aisyah (International Journal of Education, Information Technology, and Others, 2021)
This research aims at modeling how the technology of communication works within a given streaming platform. In this paper, the descriptive qualitative method was used wherein data collection is done by observing multiple channels of varying sizes on service sites such as Twitch, followed by a description of how the technology facilitates communication between the participants. The results show that there are two available methods to communicate, namely Information Resources Catalogue (IRC) chat supported by the platform, and video or audio call, which is done by external applications and funneled to the stream. These results indicate that with the website as a platform, monomodal communication can happen by text, cross-modal communication can happen by video and text, and finally, a hybrid of the cross and monomodal communication can happen wherein at least three participants are involved. Thus, this relatively new technology used by the streaming platform opens many avenues of communication.